Bioinformatics 4 - S. M. Rawoof (Ukaaz publications, 2010)
The word bioinformatics is derived from biology and informatics; the discipline of bioinformatics is rightly identified as a combination of computer science and biology.It is a computer-assisted interface discipline dealing with the acquisition, storage, management, and access and processing of molecular biology data. This discipline helps us to collect, compile, analyze, process and represent the information in order to understand processes of life, health, disease status and find new processes or better drugs delivery system for genes, drugs and other genetic components for life improvement and to educate oneself.